ADARp110 promotes hepatocellular carcinoma progression via stabilization of CD24 mRNA - Liangzhan Sun; Pengchao Hu; Hui Yang; Jun Ren; Rong Hu; Shasha Wu; Yanchen Wang; Yuyang Du; Jingyi Zheng; Fenfen Wang; Han Gao; Jingsong Yan; et al. (Proceedings of the National Academy of Sciences, 2025)
ADAR is highly expressed and correlated with poor prognosis in hepatocellular carcinoma (HCC), yet the role of its constitutive isoform ADARp110 in tumorigenesis remains elusive. We investigated the role of ADARp110 in HCC and underlying mechanisms using clinical samples, a hepatocyte-specific Adarp110 knock-in mouse model, and engineered cell lines. ADARp110 is overexpressed and associated with poor survival in both human and mouse HCC. It creates an immunosuppressive microenvironment by inhibiting total immune cells, particularly cytotoxic GZMB + CD8 + T cells infiltration, while augmenting Treg cells, MDSCs, and exhausted CD8 + T cells ratios. Mechanistically, ADARp110 interacts with SNRPD3 and RNPS1 to stabilize CD24 mRNA by inhibiting STAU1-mediated mRNA decay. CD24 protects HCC cells from two indispensable mechanisms: macrophage phagocytosis and oxidative stress. Genetic knockdown or monoclonal antibody treatment of CD24 inhibits ADARp110-overexpressing tumor growth. Our findings unveil different mechanisms for ADARp110 modulation of tumor immune microenvironment and identify CD24 as a promising therapeutic target for HCCs.